If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(15b + -10) = 5(16 + -19b) Reorder the terms: -6(-10 + 15b) = 5(16 + -19b) (-10 * -6 + 15b * -6) = 5(16 + -19b) (60 + -90b) = 5(16 + -19b) 60 + -90b = (16 * 5 + -19b * 5) 60 + -90b = (80 + -95b) Solving 60 + -90b = 80 + -95b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '95b' to each side of the equation. 60 + -90b + 95b = 80 + -95b + 95b Combine like terms: -90b + 95b = 5b 60 + 5b = 80 + -95b + 95b Combine like terms: -95b + 95b = 0 60 + 5b = 80 + 0 60 + 5b = 80 Add '-60' to each side of the equation. 60 + -60 + 5b = 80 + -60 Combine like terms: 60 + -60 = 0 0 + 5b = 80 + -60 5b = 80 + -60 Combine like terms: 80 + -60 = 20 5b = 20 Divide each side by '5'. b = 4 Simplifying b = 4
| 15=6b-6b+4b-1-6b | | -5x-25=-35 | | 5c+10d+cx-2dx=0 | | (y-4)-(y+7)=8y | | -18.4f-5.51+11.2f=-13.06+7.9f | | 13d=169 | | 4(q+3)=2(q-11) | | 1t=7 | | 2x^2=5x+5 | | 2(y-3)=2(3y+7) | | 12x^2+26x+10=0 | | 13.8+8.7n=7.2n | | 4.1s+19.96=0.5s-9.32+0.48 | | -35=7(z+3) | | (y-7)(y+4)=y-7 | | 2(p+9)-6=50 | | 10.1=-8s | | 12.2c-19.36=13.7c-8.86 | | 2x+16=6x-14 | | 5t+4=3t-2 | | t(7+t)=2(2t+5) | | -4.7-5.6q=-7.1q-18.2 | | 161x+15154*6546-56= | | 2y=3y+2b*3a | | 15-10+5q=-19+3q | | s(s-5)=36 | | 3p=25-10 | | 20g+19=19g | | 20x^2y^3-45y^3=0 | | -14k+16=-16k | | 2y^2-24y=-22 | | 1-10k=81 |